Managing hyponatremia in lung cancer: latest evidence and clinical implications. (November 2017) - Fiordoliva, Ilaria; Meletani, Tania; Baleani, Maria Giuditta; Rinaldi, Silvia; Savini, Agnese; Di Pietro Paolo, Marzia; Berardi, Rossana
Hyponatremia is the most common electrolyte disorder in lung cancer patients. This condition may be related to many causes including incidental medications, concurrent diseases and side effects of antineoplastic treatments or the disease itself. Although not frequently life-threatening, it is usually associated with prolonged hospitalization, delays in scheduled chemotherapy, worsening of patient performance status and quality of life and may also negatively affect treatment response and survival. Most of the available data focus on thoracic tumors, especially small-cell lung cancer (SCLC), where hyponatremia is frequently related to the syndrome of inappropriate secretion of antidiuretic hormone (SIADH). Few studies specifically focus on non-small cell lung cancer (NSCLC) patients. Hyponatremia treatment needs to be personalized based on severity and duration of sodium serum reduction, extracellular fluid volume and etiology. However, literature data highlight the importance of early correction of the serum concentration levels. To achieve this the main options are fluid restriction, hypertonic saline, loop diuretics, isotonic saline, tolvaptan and urea. The aim of this review is to analyze the role of hyponatremia in lung cancer patients, evaluating causes, diagnosis, management and clinical implications.